Visible-light-initiated hydrogels preserving cartilage extracellular signaling for inducing chondrogenesis of mesenchymal stem cells. (15th January 2015) - Choi, Bogyu; Kim, Soyon; Lin, Brian; Li, Kevin; Bezouglaia, Olga; Kim, Jinku; Evseenko, Denis; Aghaloo, Tara; Lee, Min
Graphical abstract: Abstract: Hydrogels have a unique opportunity to regenerate damaged cartilage tissues by introducing mesenchymal stem cells (MSCs) in a highly swollen environment similar to articular cartilage. During cartilage development, collagen–cell interactions play an important role in mediating early mesenchymal condensation and chondrogenesis with transforming growth factor-β1 (TGF-β1) stimulation. Here, a hydrogel environment that can enhance cell–matrix interactions and chondrogenesis by stabilizing type-II collagen (Col II) and TGF-β1 into photopolymerizable (methacrylated) chitosan (MeGC) with simple entrapment and affinity binding is demonstrated. The MeGC hydrogel was designed to gel upon initiation by exposure to visible blue light in the presence of riboflavin, an aqueous initiator from natural vitamin. The incorporation of Col II into MeGC hydrogels increased cellular condensation and deposition of cartilaginous extracellular matrix by encapsulated chondrocytes. MeGC hydrogels containing Col II supported the release of TGF-β1 in a controlled manner over time in chondrogenic medium and the incorporated TGF-β1 further enhanced chondrogenesis of encapsulated chondrocytes and MSCs, especially synovial MSCs. Subcutaneous implantation of hydrogel cultures showed greatly improved neocartilage formation in constructs loaded with TGF-β1 compared with controls. These findings suggest that cartilage mimetic hydrogels have a high potential for cartilage repair.